2017
DOI: 10.1111/aji.12646
|View full text |Cite
|
Sign up to set email alerts
|

The female reproduction and senescence nexus

Abstract: Successful pregnancy is regulated by several soluble factors that are differentially expressed throughout gestation. These factors are important to initiate and establish embryo implantation and parturition. Senescent cells, which undergo permanent cell proliferation arrest in response to stress, also produce several secreted factors, referred to as the senescence-associated secretory phenotype (SASP). Here, we review some of the secreted factors found during early and late pregnancy and compare their expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…Thence, it is very likely that males with pre-existing comorbidities of inflammatory nature must be at higher risk of further inflammation-related complications. On the other hand, females seem to be constitutively protected against pro-inflammatory senescence-associated cytokines [ 50 ], which might render women less susceptible of developing most of the severe forms of COVID-19, as we shall discuss next. Interestingly, although the virus-induced direct cytopathic effects can play a role in the deleterious clinical manifestations of SARS, the exuberant innate immune response against virus is thought to be responsible for the high rates of mortality involving exacerbated inflammatory response [ 30 ].…”
Section: Chronic Suppression Of the Physiological Resolution Of Inflamentioning
confidence: 99%
See 1 more Smart Citation
“…Thence, it is very likely that males with pre-existing comorbidities of inflammatory nature must be at higher risk of further inflammation-related complications. On the other hand, females seem to be constitutively protected against pro-inflammatory senescence-associated cytokines [ 50 ], which might render women less susceptible of developing most of the severe forms of COVID-19, as we shall discuss next. Interestingly, although the virus-induced direct cytopathic effects can play a role in the deleterious clinical manifestations of SARS, the exuberant innate immune response against virus is thought to be responsible for the high rates of mortality involving exacerbated inflammatory response [ 30 ].…”
Section: Chronic Suppression Of the Physiological Resolution Of Inflamentioning
confidence: 99%
“…Female physiology developed a hormonally-mediated antisenescent program different from that of males. For example, SASP components are produced during the phases of pregnancy, including the inflammation-like driven parturition response [ 50 , 139 ]. Nevertheless, this does not influence fetus health or labor and there are no signs of cellular senescence or SASP-related chronic inflammatory disease in females after parturition [ 50 ].…”
Section: The Physiological Antisenescent Program In Womenmentioning
confidence: 99%
“…Collagen deposition in tissues occurs as a result of chronic inflammatory processes involving several pathways: inflammatory interleukins, growth factors, caspases, oxidative stress products, and accumulation of senescent cells [7]. These chronic inflammatory pathways are also involved in undesired obstetric outcomes such as loss of pregnancies and preterm delivery [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular senescence is one of the hallmark of aging process and can be defined as an irreversible and stable arrest of the cell cycle causing inflammation through a complex senescence-associated secretory phenotype (SASP) (Perrott et al 2017;Lawrence et al 2018). Studies have reported that senescent cells and inflammation are implicated in general age-related dysfunction (Lawrence et al 2018), including in female reproductive organs (Marquez et al 2017;Shirasuna and Iwata 2017, for reviews). It might be interesting to investigate whether SASP processes are involved in the ageinduced alteration of the central regulation of the preovulatory LH surge.…”
Section: Discussionmentioning
confidence: 99%